2008
DOI: 10.1161/hypertensionaha.107.107672
|View full text |Cite
|
Sign up to set email alerts
|

Wine Polyphenols Improve Endothelial Function in Large Vessels of Female Spontaneously Hypertensive Rats

Abstract: Abstract-Red wine polyphenols (RWPs) have been reported to prevent hypertension and endothelial dysfunction.Several individual RWPs exert estrogenic effects. We analyzed the possible in vivo protective effects on blood pressure and endothelial function of RWPs in female spontaneously hypertensive rats (SHR) and its relationship with ovarian function. RWPs (40 mg/kg by gavage) were orally administered for 5 weeks. Ovariectomized rats showed both increased isoprostaglandin F 2␣ excretion and aortic superoxide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 59 publications
3
47
1
1
Order By: Relevance
“…48 Moreover, our results clearly showed that red wine and de-alcoholized red wine significantly decreased SBP and DBP in the MetS patients and these results agree with those of other studies, which have reported that polyphenols reduce elevated blood pressure. 49 Interestingly, polyphenols and polyphenols plus ethanol significantly reduced the blood glucose levels in the MetS patients compared to baseline, possibly due to the shift in the gut microbiota to a higher proportion of Gram-positive relative to Gram-negative bacteria produced by the presence of polyphenols. It has been found that type 2 diabetes mellitus might be associated with the dominance of Gram-negative bacteria in the gut.…”
Section: Food and Function Papermentioning
confidence: 92%
“…48 Moreover, our results clearly showed that red wine and de-alcoholized red wine significantly decreased SBP and DBP in the MetS patients and these results agree with those of other studies, which have reported that polyphenols reduce elevated blood pressure. 49 Interestingly, polyphenols and polyphenols plus ethanol significantly reduced the blood glucose levels in the MetS patients compared to baseline, possibly due to the shift in the gut microbiota to a higher proportion of Gram-positive relative to Gram-negative bacteria produced by the presence of polyphenols. It has been found that type 2 diabetes mellitus might be associated with the dominance of Gram-negative bacteria in the gut.…”
Section: Food and Function Papermentioning
confidence: 92%
“…Although many ACE inhibitors derived from foodstuffs have been identified in the past (7), only a few reports on natural renin inhibitors were available (6,11,20,21). Studies have supported that polyphenol-containing materials such as black and green tea (14), red wine (12), cocoa extract (5,17) and azuki bean seed coats (13) could reduce blood pressure in several experimental hypertensive models. The mechanisms underlying this effect were proposed to be attributable to vasodilator action, the attenuation of vascular oxidative stress and inflammation, and the ability to reduce arginase-2 activity (18), as well as the inhibitory effect against ACE (1,3).…”
mentioning
confidence: 99%
“…Polyphenols might protect the cardiovascular system by a variety of actions, including their ability to improve the lipid profile; dilate blood vessels by stimulating the endothelial formation of NO, and also in some blood vessels EDHF, and by their antioxidant properties, which will prevent the degradation of NO by superoxide anions (Sarr et al 2006;Stoclet et al 2004;Frankel et al 1993;Fitzpatrick et al 2000;Madeira et al 2009;Mann et al 2007;Ndiaye et al 2005). In addition, polyphenol-rich sources such as a red wine extract have been shown to reduce systolic blood pressure and to improve endothelial dysfunction in several experimental models of hypertension (Sarr et al 2006;Lopez-Sepulveda et al 2008;de Moura et al 2004;Bernatova et al 2002;Schini-Kerth et al 2010). Altogether, these findings support the view that polyphenol-rich natural products may protect the cardiovascular system, in part, by improving the endothelial function and, hence, retarding the development of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 81%